MENGUKUR DERAJAT JENIS DAN FUNGSI DALAM HIRARKI PERATURAN PERUNDANG-UNDANGAN PASAL 7 (4) UNDANG-UNDANG NO. 10 TAHUN 2004 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Noor Tri Hastuti (Perspektif, 2007)
The error, overlapping and the error of the arrangement of the legislation in finishing law problem in the form a group and in the state, can be minimize by understanding kind, function, material content authority hierarchy and also the arrangement of the legislation.The regulation No. 10/2004, appears as the Progress that give orientation, standard for the regulation maker and the up holder of law in Indonesia. Never the less, there is some thing that have to be analyzed deeply and decide the degree of the kind of the legislation arrangement in which it is explained in section 7 (1) jo section 7 (4) jo section 7( 5) about the kind and the hierarchy of the legislation arrangement in Indonesia.The decision of the position of the legislation arrangement in hierarchy of the legislation arrangement is placed in the context of the formal valid of the legislation arrangement such as Lex superior Derogat Lex Inferior Lex Specialis Derogat Lex Generalis and also Lex posteriori Derogat Lex Priori. So the decision of the position of the legislation arrangement is devised based on the legislation arrangement which command in the hierarchy of the legislation arrangement.